Physicochemical and structural properties of three pectin fractions from muskmelon (Cucumis melo) and their correlation with juice cloud stability. (March 2022) - Pan, Xin; Zhao, Wenting; Wang, Yuxiao; Xu, Yingying; Zhang, Wentao; Lao, Fei; Liao, Xiaojun; Wu, Jihong
Abstract: Pectin is one of the crucial endogenous components in cloudy juice and easily affects cloud stability due to its stabilizing property. To obtain improved cloud stability, the physicochemical and structural characteristics of pectin fractions from muskmelon and their correlation with juice cloud stability were investigated. In this study, a water-soluble pectin fraction, a trans -cyclohexane-1, 2-diaminetetraacetic acid (CDTA)-soluble pectin fraction, and a sodium carbonate-soluble pectin fraction were sequentially extracted from the whole muskmelon fruits. All pectin fractions were classified as low-methoxy pectin and contained 3.06–8.26% protein. Measurements of the monosaccharide compositions and microstructure showed that CDTA-soluble pectin and water-soluble pectin consisted of aggregates of linear homogalacturonan, whereas sodium carbonate-soluble pectin was more highly branched. Analysis of Fourier transform infrared and nuclear magnetic resonance spectroscopy revealed observable differences between the chemical structures of the three pectin fractions. Thermogravimetric analysis indicated sodium carbonate-soluble pectin had the highest thermal stability than other pectin. Of all pectin fractions, CDTA-soluble pectin had the highest molecular weight, which resulted in the highest apparent viscosity. Moreover, the principal component analysis showed that CDTA-soluble pectin played an important role in cloud stability. This study will provide valuable information for the melon juice industry with regard to the utilization of pectin to improve cloud stability. Graphical abstract: Three pectin polysaccharide fractions were sequentially extracted from whole muskmelon fruits. All pectin fractions showed different chemical structures. CDTA-soluble pectin played an important role in the cloud stability. Image 1 Highlights: ● Three pectin polysaccharide fractions were isolated from whole muskmelon fruits. ● Obvious differences in chemical structures of three pectin were observed. ● Chelator-soluble pectin showed higher molecular weight and apparent viscosity. ● Sodium carbonate-soluble pectin exhibited the highest thermal stability. ● Cloud stability was strongly correlated with chelator-soluble pectin.